1977
DOI: 10.1159/000178800
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Pancreatic Polypeptides (APP and BPP) to Return to Normal the Hyperglycaemia, Hyperinsulinaemia and Weight Gain of New Zealand Obese Mice

Abstract: Intraperitoneal injections of avian pancreatic polypeptide (APP) and bovine pancreatic polypeptide (BPP) are capable of returning to normal the hyperinsulinaemia, hyperglycaemia and weight gain of New Zealand obese mice. The lag glucose tolerance also becomes indistinguishable from normal. The mechanism whereby these polypeptides cause reversion is not known. Reversion can also be brought about by the intraperitoneal implantation of islets from white mice into New Zealand obese animals. The implanted islets se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(14 citation statements)
references
References 9 publications
(12 reference statements)
2
11
1
Order By: Relevance
“…Although earlier studies suggested a possible defect in the development of pancreatic peptide-positive (PP) cells in the islets of NZO/Wehi mice (Gates and Lazarus, 1977;Gates et al, 1972Gates et al, , 1974, we observed numerous granulated PP-cells, as well as glucagoncontaining alpha cells. Although less numerous, somatostain containing delta cells were also demonstrable by immunochemical staining (Fig.…”
Section: Junger Et Alcontrasting
confidence: 92%
See 1 more Smart Citation
“…Although earlier studies suggested a possible defect in the development of pancreatic peptide-positive (PP) cells in the islets of NZO/Wehi mice (Gates and Lazarus, 1977;Gates et al, 1972Gates et al, , 1974, we observed numerous granulated PP-cells, as well as glucagoncontaining alpha cells. Although less numerous, somatostain containing delta cells were also demonstrable by immunochemical staining (Fig.…”
Section: Junger Et Alcontrasting
confidence: 92%
“…An alloimmune rejection would be anticipated across this major histocompatibility barrier. Further, the observation that NZO islets are rich in PP cells refutes an earlier suggestion that there is a genetic lack of PP, and further makes it unlikely that PP from other islet sources would be curative, as reported previously (Gates and Lazarus, 1977).…”
Section: Junger Et Alsupporting
confidence: 83%
“…Although the half-life is of the order of 5 min the levels remain increased for several hours, indicating a continuous release (8). Injections ofbovine PP (bPP) decrease food intake and body weight in the hyperglycemic ob/ob mouse (9), and injections of either the bovine or avian PP (aPP) cause New Zealand obese mice to revert to normal (10). Although these observations indicate that PP may act as a satiety factor, the peptide appears to have other physiological effects in addition, including increased gut motility and "gastrin-like" actions (11,12).…”
mentioning
confidence: 99%
“…injection reduces food intake and weight gain in ob/ob mice [160]. In New Zealand obese mice, similar treatment reduces hyperglycaemia, hyperinsulinaemia and weight gain [162]. More recent studies have shown that mice with selective transgenic overexpression of PP in pancreatic islets, resulting in a 20-fold increase in plasma PP concentration, are lean and hypophagic in comparison with controls [163].…”
Section: Pancreatic Polypeptidementioning
confidence: 99%